1999
DOI: 10.1074/jbc.274.47.33531
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Amino Acid Sequence in the Hinge Region of Human Vitamin D Receptor That Transfers a Cytosolic Protein to the Nucleus

Abstract: The localization of human vitamin D receptor (VDR) in the absence of its ligand 1,25-dihydroxyvitamin D 3 was investigated using chimera proteins fused to green fluorescent protein (GFP) at either the N or C terminus, and the nuclear localization signal (NLS) was identified. Plasmids carrying the fusion proteins were transiently or stably introduced into COS7 cells, and the subcellular distribution of the fusion proteins was examined. GFPtagged wild-type VDRs were located predominantly in nuclei but with a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
31
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 46 publications
6
31
0
Order By: Relevance
“…3, compare D with B), the distinct ligand response of VDRnlsm suggests that, unlike RXR whose nuclear translocation relies solely on the DBD-NLS, VDR contains an additional, ligand-responsive NLS. These observations are thus in agreement with previous reports indicating that VDR harbors more than one functional NLS (21,23).…”
Section: Generation Of Gfp-rxr and Bfp-vdr-to Enable Imaging Of Rxrsupporting
confidence: 83%
See 1 more Smart Citation
“…3, compare D with B), the distinct ligand response of VDRnlsm suggests that, unlike RXR whose nuclear translocation relies solely on the DBD-NLS, VDR contains an additional, ligand-responsive NLS. These observations are thus in agreement with previous reports indicating that VDR harbors more than one functional NLS (21,23).…”
Section: Generation Of Gfp-rxr and Bfp-vdr-to Enable Imaging Of Rxrsupporting
confidence: 83%
“…It was thus reported that the glucocorticoid receptor harbors an additional NLS within its LBD, and that this sequence possesses a different importin selectivity than that displayed by the NL1 (22). VDR appears to harbor a bipartite NLS in the stretch between residues 67 and 108 (21) and another NLS in its hinge region (23).…”
mentioning
confidence: 99%
“…We found earlier that the cytoplasmic portion of VDR-GFP also translocates into the nucleus in a ligand-dependent fashion (5,6). The mechanisms controlling VDR translocation, however, remained to be elucidated.…”
mentioning
confidence: 99%
“…Recently we and others have used green fluorescent protein chimeras of VDR to study the receptor distribution in living cells (5)(6)(7). Unlike the glucocorticoid receptor (GR), which stays in the cytoplasm without the ligand, the unliganded VDR distributes evenly between the cytoplasm and the nucleus.…”
mentioning
confidence: 99%
“…The deletion of VDR in the enterocyte results in a 70% reduction in intestinal calcium absorption efficiency that is coincident with a significant reduction in CaBPD9k, TRPV6, and PMCA1b gene expression [Van Cromphaut et al, 2001;Song et al, 2003a].Previous research shows that binding of 1,25(OH) 2 D 3 to VDR in the cytoplasm of cells stimulates heterodimerization of VDR with RXR and the redistribution of the VDR-RXR-hormone complex to the nucleus [Barsony et al, 1990;Michigami et al, 1999;Racz and Barsony, 1999;Sunn et al, 2001]. The nuclear import of the VDR-RXR-hormone complex is active [Racz and Barsony, 1999;Miyauchi et al, 2005], enhanced by 1,25(OH) 2 D 3 treatment [Michigami et al, 1999;Racz and Barsony, 1999;Sunn et al, 2001], dependent upon the presence of intact nuclear localization sequences (NLSs) in both VDR and RXR [Prufer et al, 2000], and requires various importins [Miyauchi et al, 2005;Yasmin et al, 2005]. Most of the studies examining the mechanism of VDR nuclear import have been conducted in COS-7 kidney cells (characterized by low expression of endogenous VDR) and some characteristics of VDR import have been confirmed in cells from bone, skin, or kidney.…”
mentioning
confidence: 99%